Risk factors associated with equine piroplasmosis with varying clinical manifestations - P.I.Ganesan (The Indian Veterinary Journal, 2023)
Equine puiroplasmosis is considered as an important disease in India.It is a tick borne disease caused by blood protozoan parasites Babesia equi and Babesia caballi.Two Irish draught and Thorough breds cross, male horses, 6 years old, were presented to the veterinary clinical complex, Apollo College of Veterinary Medicine, Jaipur with clinical condition of pyrexia, (103.5),lethargy,poor performance ,poor weight gain ,exercise intaleranceand anorexia since 45 days.In this clinical study, both horses were icteric, anemia of the eye mucus membrane. Coughing, mild nasal discharge, labored breathing, moist rales with pleuretic rub on lung auscultation, muffling heart sounds (60 per minute), edema of fetlockjoint and pastoral region, dragging of the left hind leg. Exercise intolerance was pronounce in both infected horses. Blood smear examination and haematological parameters indicated the presence ofBabesia equi.The risk factors associated for infection of B.equi in the absence of tick infestations were concluded to be due to rearing of equines along with the free roaming dogs and dairy cows inside the farm premises and absence of regular deticking program for all the farm animals.